Pemberdayaan Masyarakat Dalam Upaya Menekan Angka Kejadian Hipertensi Menggunakan Tanaman Pakcoy dan Seledri Sebagai Alternatif Penurun Hipertensi di Wilayah Dusun Citangkolo Desa Kujangsari - Adhynda Maulyna Duta Mahardyka; Iqbal Septianto Hilmi; Salma Waisya Turfah; Ruhyatin Nisfu Ramdhani; Nurul Azizah; Nadiva Tasya Qurrotuaini; Ratu Dhia Ulhaq; Annisa Nurul Aikah; Aldian Dwi Fartisan; Intan Aulia Almaida; Andy Muharry (ARDHI : Jurnal Pengabdian Dalam Negri, 2024)
Hypertension is defined as persistent blood pressure with a systolic pressure ≥140/90 mmHg. Hypertension is one of the risk factors that most influences the incidence of heart disease, blood vessels and stroke. Hypertension often shows no symptoms, so it is only realized when it has caused organ disorders such as heart dysfunction or stroke. One of the causes of hypertension is unhealthy lifestyle factors, one of which is a lack of vegetable consumption which has the risk of causing hypertension. Based on Field Learning Practice (PBL) 1 activities, namely community diagnosis in Citangkolo Hamlet, Kujangsari Village, Langensari District, Banjar City, in 2023, a priority health problem was found, namely hypertension, with the number of sufferers reaching a percentage of 54% of the total 231 people. This is due to the lack of vegetable consumption in the community. Based on this problem, PBL 2 activities were carried out, by carrying out innovative intervention activities for the SI ELNINO program (Alternative Intervention for Citangkolo Hypertension Reducing Plants) which was carried out so that people would pay more attention to consumption patterns by planting pak choy and celery vegetables as a form of control, namely reducing the blood pressure of hypertension sufferers. . This activity is carried out in the form of counseling and providing education, Training of Trainers, and planting by empowering the Women Farmers Group (KWT) with a vegetable planting movement. This activity was attended by posbindu cadres, KWT, and the Citangkolo hamlet community. Through outreach activities there is a significant increase in public knowledge regarding hypertension as proven by the results of the pretest and posttest with a p-value <0.001. So this activity has succeeded in increasing the knowledge of the Citangkolo hamlet community regarding hypertension.